(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Edema and swelling of the brain (OCS) is one of the main causes of mortality in traumatic brain injury [1], neuroinfections, and liver failure [2, 14]. Also, cerebral edema is observed with tumors of the central nervous system, cerebral circulatory disorders, intoxication, and complicates some mental and infectious diseases, renal failure, and hypoxic conditions [3]. For example, mortality in severe traumatic brain injury (TBI) reaches 70% [4], while, according to various authors, swelling and dislocation of the brain are the main cause of death (about 40% of cases) [5,6]. Therefore, ONGM remains one of the main problems of intensive care.